Research on the Influence Mechanism of Enterprises’ Participation in School Enterprise Cooperation Based on the Analysis Framework of Theory of Planned Behavior - Zhang, Yuanbao; Wang, Junbin; Shen, Xiangdong; Song, Jinyu (Frontiers in Psychology, 2022)
School enterprise cooperation, as the basic school running form of applied undergraduate education, is an important way to cultivate high-level applied talents. However, the lack of motivation for enterprises to participate in school enterprise cooperation and the resulting problem of "school hot and enterprise cold" seriously restrict the in-depth cooperation between schools and enterprises in China's application-oriented universities. There is an urgent need to explore the influencing factors and mechanism of enterprises' participation in school enterprise cooperation. Unlike previous studies, taking Ajzen’s (2002) Theory of Planned Behavior (TPB) as the theoretical framework, this study constructs the influencing factor model of enterprise participation in school enterprise cooperation from four aspects: behavior attitude, subjective norms, perceived behavior control and behavior intention. In this study, participants (N= 250) completed a questionnaire assessing their participation in school enterprise cooperation, which was analyzed by structural equation model (SEM). The results show that the behavior attitude and perceived behavior control of enterprises have a significant positive impact on their intention to participate in school enterprise cooperation, and then have a significant positive impact on the school enterprise cooperation behavior of enterprises. The behavior intention and perceived behavior control of enterprises have a significant positive impact on their participation in school enterprise cooperation. The policy environment has a significant regulatory effect on the relationship between the intention and behavior of enterprises’ participation in school enterprise cooperation. Therefore, from the perspective of enhancing the intention of enterprises to cooperate, colleges and universities should establish the awareness of win-win cooperation and meet the reasonable interest demands of enterprises in school enterprise cooperation, so as to improve the behavior attitude and intention of enterprises. From the perspective of the formation conditions of school enterprise cooperation, with the help of industry associations, an information service platform for school enterprise cooperation should be built, so as to eliminate the information islands between enterprises and universities. From the perspective of the needs of school enterprise cooperation environment, government departments should strengthen policy support for school enterprise cooperation in order to eliminate the worries of enterprises.